Penerapan Model Pembelajaran Berbasis Proyek Menggunakan Trello untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP Pertiwi Cilimus (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of a project-based learning model using Trello to improve the learning outcomes of seventh-grade students at SMP Pertiwi Cilimus. The method used in this research is a quantitative method with a pre-experimental research approach. The population of this study consists of all seventh-grade students of SMP Pertiwi Cilimus, with a sample of 22 students from class VII A, comprising 14 male students and 8 female students. The data collection techniques used include observation and pre-test post-test. The data analysis technique used is quantitative data analysis, specifically the t-test. The research results show a significant increase in student learning outcomes. This is evidenced by the increase in the average student score from 72.27 in the pre-test to 81.14 in the post-test. This difference is statistically significant through the results of the Paired Sample T-Test (Sig. = .000). It can be concluded that the application of the project-based learning model assisted by Trello has a significant effect on improving the learning outcomes of students in class VII A of SMP Pertiwi Cilimus.